(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
The intention of this article is to focal point on advertising and marketing discourse. Advertising is an extremely versatile and multifaceted phenomenon that occupies a border function between one-of-akind professions and attracts the interest of representatives of exceptional professions. In linguistics, advertising and marketing is a very wise use of methodological skill in discourse. The most stringent requirement for advertising discourse is to grant maximum data in minimal words. The most important factor of advertising is text. The unit of advertising textual content is the word. Furthermore, we can add that, the word is the most essential linguistic unit, due to the fact it has a meaning and contains statistics, vital data about objects and their properties. The essential system of growing an commercial is the introduction of an commercial template, which consists of careful resolution of the phrases used in the advertisement.